Comparison of the dosimetric response of 4-element BeOSL and TLD-100 passive personal dosimeters. (September 2016) - Oliver, L.; Candela, C.; Palma, J.D.; Pujades, M.C.; Soriano, A.; Alabau, J.; Martínez, J.; Mestre, V.; Ruiz, J.C.; Vilar, J.; Llorca, N.
Abstract : Introduction: Thermoluminescent dosimeters (TLD-100, ThermoFisher-Scientific, USA) and optically stimulated dosimeters based on beryllium oxide (BeOSL, Dosimetrics GmbH, Germany) are passive personal dosimeters. Purpose: The aims of this study were to verify that the 4-element version of both systems satisfy the IEC-62387 dosimetric requirements, and to compare them. Materials and methods: The TLDs tested were those provided by the National Dosimetry Centre (CND), with a home-made dose calculation algorithm, whereas BeOSLs were as distributed by Dosimetrics. The tests performed were: coefficient of variation, non-linearity, photon angular and energy dependency, reusability and time dependency, as well as detection threshold and energy estimation accuracy. Results: Both systems satisfy the IEC-62387 requirements for the tests described above. Among the advantages of BeOSLs, these have lower energy dependency (Hp(10) accuracy is better than 11% between 16.1 keV and 662 keV) and can be read more than once with good accuracy when re-reading correction is applied (<3% variation beyond 1 mSv between at least 5 consecutive re-readings). Also, each dose value provided is the average of 5 measurements, with a consistency check. However, the CND dose algorithm for TLDs provides more accurate energy estimations, which are used to correct their higher energy dependency. In addition, TLD readers provide glow curves that can be used to identify misreading of any of the 4 elements. Conclusion: The TLDs and BeOSLs tested satisfy the dosimetric requirements to be used as personal dosimeters. The choice between one of them might depend on the importance given to the different criteria studied.